(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
An enrollment system unifies all of the operations involved in the enrollment process into one system. Everything happens in one place, both online and offline, in this manner. The prospects were discussed, as were the pages they were visiting, their interests and motives, their personal information, and the meetings they had arranged, to name a few. An enrollment system’s overall goal is to assist admissions staff in enrolling more students. It is one of our schools or universities’ most important subjects. Enrollment systems are used to track a student’s information. All information on the parents is easily accessible. Making the Enrollment Management System (EMS), the researchers analyze and examine the system’s whole meaning. The researchers planned an enrollment management system to make enrolling easier for students and teachers. The researchers analyze and process the student enrollment requirements in the analysis phase. When it comes to design, simple designs are done. The researchers will scan some errors in the testing phase before releasing the system. To implement the system, users must use it on their devices while the researchers will run a seminar to gain knowledge of the system. While users operate the system, maintenance will be performed when users find some unexpected errors. Users can notify the programmer for maintenance service.